Universal Health Coverage for Inclusive and Sustainable Development : Country Summary Report for Indonesia - Marzoeki, Puti; Tandon, Ajay; Bi, Xiaolu; Pambudi, Eko Setyo (World Bank Group, Washington, DC, 2014)
Indonesia, a low-middle income country of around 242 million people, has made impressive gains in health over the past few decades, notably in increased life expectancy and reduced infant and child mortality rates. There has been less progress in improving maternal mortality and malnutrition. Inequities among geographic areas and income levels are large, presenting a major challenge to the health care system. Demographic and epidemiological transitions have affected the disease burden: disability-adjusted life-years (DALYs) due to cerebrovascular disease, cardiovascular diseases, diabetes, and lung cancer have increased by 80 percent or more during 1990 2010. The central government has committed to achieving universal health coverage (UHC) by 2019 as projected in the Road Map of the Jaminan Kesehatan Nasional (JKN), or National Health Insurance Program, 2012-2019.